Determinación de un método simplificado para la inspección estructural de edificaciones de concreto reforzado - Chimbo Bayas, Rubén Darío (2020)
Ecuador is in one of the most active seismic zones on the planet, proof of this is the recent earthquake that occurred on April 16, 2016 on the Ecuadorian coast of magnitude 7.8 Mw causing the destruction of the downtown commercial area of Portoviejo city, with which the present investigation arises that focuses on the inspection of reinforced concrete buildings through the application of an own inspection instrument comparing foreign and national methods, in order to couple it to the Ecuadorian Construction rule (NEC) , and in this way be able to determine its behavior. According to the methodology used, the research classified as applied with a field design for buildings between 2 to 7 floors, where for its validation a technical inspection was carried out on buildings of the National University of Chimborazo and compared with the results included from the Italian method of the seismic vulnerability index modified by Dr. Aguiar, including within the analysis, the conception of the structural configuration, configuration of structural elements, seismic behavior, location risk, and damage from previous incidents. The result of the proposed method shows that despite having buildings with earthquake resistant design, some of these present small problems, due to ineffective designs with previous standards, limiting their resistance capacity. The percentage values obtained from the proposal do not exceed 10.09%, and with the Italian method the values obtained were null except for Block A central segment, which was less than 12.2%, determining as safe buildings, which is not requires the application of inspections or additional evaluations to these.